Evidenciação dos instrumentos financeiros: uma investigação nas empresas listadas no nível 1 de governança corporativa da BM&FBovespa - Oliveira Neto, Francisco Helder de (2015)
This study looked at the disclosure level of the companies listed on the BM&FBovespa on the measurement of financial instruments. With regard to methodological aspects, the research was classified as qualitative, descriptive, documentary and bibliographic, and a sample of 23 companies listing segment Level 1 of Corporate Governance. The disclosure of the measurement in the notes was analyzed from the requirements of CPC 38 (R6), 39 and 40, summarized in a checklist. And the main results showed that the higher disclosure rate of companies was 100%, and the lowest was 40%. In addition, it was noted that the best disclosure levels were present in electric utilities, assuming tightening the requirements by the regulatory agency. The most constant items (100% of companies showed) were related to the price of fair value and the extent of risks where instruments were involved, items with essential information to the subject. In general, the companies analyzed showed a good level of disclosure, when around 82% of the sample reported more than half of the items that were required at check list.